KADAR VITAMIN C DAN ORGANOLEPTIK MANISAN BASAH LIDAH BUAYA (Aloe vera) PADA KONSENTRASI AIR KAPUR (Ca(OH)2) YANG BERBEDA - Ike Apriani; Meli Yani (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2018)
Aloe vera is one species of Liliaceae that is able to grow in tropic area such as Indonesia. Aloe verahas potential as food, such as sweets. The slimy and soft texture of Aloe vera makes the problem of producing quality sweets products so it needs soaking with Ca(OH)2 solution.This study aims to determine the content of vitamin C and organoleptic in Aloe vera sweets with various concentrations of Ca(OH)2 solution. The research was conducted in March 2017 at Biology and ChemistryLaboratory,FTIKRaden Fatah State Islamic University. This research use experimental method, through experiment design used RAL one factor with concentration of Ca(OH)2 solution, consist of K1 = 1%, K2 = 2%, K3 = 3% and K4 = 4% (5 repetitions). Research method using titration and hedonic method. The highest vitamin C levels were found in the treatment with the concentration of Ca(OH)2 1% solution ie 323.84 mg/100gr. Organoleptic test results obtained concentration of Ca(OH) 24% solution preferably by panelist.